MicroRNA-451 is downregulated in the follicular fluid of women with endometriosis and influences mouse and human embryonic potential - Xiong Li; Wenbi Zhang; Jing Fu; Yan Xu; Ruihuan Gu; Ronggui Qu; Lu Li; Yijuan Sun; Xiaoxi Sun (BMC, 2019)
Abstract Background Previous work demonstrated that there are numerous miRNAs in human follicular fluids, some of which are associated with reproductive diseases. In the current study, we sought to determine whether microRNAs (miRNAs) in the follicular fluid (FF) are differentially expressed between women with and without endometriosis and to uncover the association of miRNAs with the oocyte and embryonic development potential. Methods FF was harvested from 30 women with endometriosis and 30 women without who underwent in vitro fertilization treatment at the University Hospital between February and December 2016. The FF samples were subjected to miRNA profiling and validation via quantitative reverse transcription polymerase chain reaction analysis. Mouse/human metaphase-I (MI) oocytes were harvested and micro-injected with an miR-451 inhibitor, and the effects of miR-451 knockdown on Wnt/WNT signalling genes were investigated. Results Oocyte number, fertilization rate, and number of available embryos were decreased significantly in women with endometriosis relative to those without endometriosis. Hsa-miR-451 in FF was downregulated in endometriosis patients relative to control subjects (P < 0.01). Moreover, the proportions of mouse/human MI oocytes that developed into 2-pronuclei (2PN), 2-cell, 8-10-cell and blastocyst-stage embryos were affected by miR-451 knockdown in mouse/human oocytes. Components of the Wnt signalling pathway were aberrantly expressed in the mouse/human oocytes and embryos in the miR-451 inhibitor-injected group. Conclusions miR-451 was downregulated in FF samples from endometriosis patients and was modestly effective in distinguishing endometriosis patients from non-endometriosis patients. miR-451 downregulation in mouse and human oocytes affected pre-implantation embryogenesis by suppressing the Wnt signalling pathway. This miRNA might serve as a novel biomarker of oocyte and embryo quality in assisted reproductive treatment.